Yang-Lee zeros of the two- and three-state Potts model defined on π3 Feynman diagrams - Albuquerque, Luiz C. de [UNESP]; Dalmazi, D. [UNESP] (Amer Physical Soc, 2003)
We present both analytical and numerical results on the position of partition function zeros on the complex magnetic field plane of the q=2 state (Ising) and the q=3 state Potts model defined on phi(3) Feynman diagrams (thin random graphs). Our analytic results are based on the ideas of destructive interference of coexisting phases and low temperature expansions. For the case of the Ising model, an argument based on a symmetry of the saddle point equations leads us to a nonperturbative proof that the Yang-Lee zeros are located on the unit circle, although no circle theorem is known in this case of random graphs. For the q=3 state Potts model, our perturbative results indicate that the Yang-Lee zeros lie outside the unit circle. Both analytic results are confirmed by finite lattice numerical calculations.
Keywords: Calculations; Convergence of numerical methods; Correlation methods; Eigenvalues and eigenfunctions; Graph theory; Magnetic fields; Mathematical models; Random processes; Temperature; Feynman diagram; Ising model; Random graph; Three-state Potts model; Two-state Potts model; Yang-Lee zeros; Statistical mechanics